2018
DOI: 10.3390/nano8060387
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Frictional Properties of Single-Layer Molybdenum-Disulfide Film Based on a Coupling of Tip Radius and Tip–Sample Distance by Molecular-Dynamics Simulations

Abstract: Lateral-force microscopy is a powerful tool to study the frictional properties of two-dimensional materials. However, few works distinctly reveal the correlation between the tip radius with the tip–sample distance and the frictional properties of the two-dimensional (2D) materials. We performed molecular-dynamics simulations to study the atomic-scale friction of a typical two-dimensional single-layer molybdenum disulfide (SLMoS2). The effects of tip radius and tip–sample distance on the frictional properties w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…However, it should be noticed that because of lattice structure the lower peaks additionally appear to interleave the higher peaks in the friction force curves as seen in this work (Fig. 4) and the work of Pang et al [24] that simulated the atomic-scale friction of a typical two-dimensional singlelayer molybdenum disulfide. This work also states that at micron-scale there is a little difference of the average friction and normal forces between the CG Al2O3 and Fe2O3 oxides.…”
Section: Resultssupporting
confidence: 54%
“…However, it should be noticed that because of lattice structure the lower peaks additionally appear to interleave the higher peaks in the friction force curves as seen in this work (Fig. 4) and the work of Pang et al [24] that simulated the atomic-scale friction of a typical two-dimensional singlelayer molybdenum disulfide. This work also states that at micron-scale there is a little difference of the average friction and normal forces between the CG Al2O3 and Fe2O3 oxides.…”
Section: Resultssupporting
confidence: 54%
“…However, the vacancy defects, known as the most commonly reported defects in graphene [20,21] and SLMoS 2 [22,23], are inevitable during the production process and can result in considerable changes in surface morphology. So far, most experimental, theoretical, and simulation studies on the atomic-scale friction of graphene and SLMoS 2 have focused on atomically flat surfaces [24][25][26][27][28]; nevertheless, these simplified idealizations cannot reflect the topography and frictional properties of many practical surfaces such as vacancy-defective surfaces. Molecular dynamics (MD) simulations have indicated that the frictional forces of defective graphene were significantly increased in the vicinity of vacancy point defects compared to that of the perfect graphene [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…In general, sample topography recorded by an AFM is considered to be more exquisite with a sharper tip. [11][12][13] However, the tip-sample interaction for silicon tips 14) during AFM scanning and indentation experiments inevitably causes tip wear, though carbon nanotube tips and diamond-coated tips are quite resistant to wear. 15,16) The tip wear may enlarge the tip radius gradually, and the AFM imaging resolution and quality become degraded.…”
Section: Introductionmentioning
confidence: 99%
“…17) Besides, it is difficult when only using the AFM force curves to measure or control the tip-sample distance in an actual experiment for the reasons that various component forces, such as Coulomb (electrostatic), 18) van der Waals (dispersion), 19) atomic 20) and dipole forces, 21) are exerted by sample atoms on the tip, and these force curves remarkably differ from each other. 11) Many endeavours have been devoted to testing the ultrahigh resolution of AFM through modifying the tip apex or state. [22][23][24][25] However, they emphasized their works on the effects of tip apex on imaging a single atom or cluster on the substrate and did not move the tip parallel to the sample surface with different vertical distance between the surface and the tip.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation